The Implementasi Network Automation Pada GNS3 Untuk Otomasi Konfigurasi Di PT. Semut Merah Squad - Firmansyah, Iqbal (Buletin Ilmiah Informatika Teknologi, 2024)
PT. Semut Merah Squad (J&T Express) is a goods delivery company founded in 2015. This company adopts technology as the main foundation in its operational system. One of the important components in the integrated IT system at J&T Express is network management which has a high level of complexity. Network management at J&T Express currently still relies on manual processes when configuring network devices. This results in time inefficiency in the process of configuring network devices. Based on the problems that occurred at J&T Express, implementing network automation is a solution to overcome network management, one of which is configuration which is still done manually and one by one when deploying devices. The aim of this research is to measure the effect of implementing network automation as a technology in managing network devices automatically. This research method uses a qualitative research method by creating a network automation design or prototype on GNS3 using the Python programming language. After that, analysis and testing is carried out to verify the correctness and effectiveness of the designed network automation. This research method uses a qualitative research method by creating a network automation design or prototype on GNS3 using the Python programming language. After that, analysis and testing is carried out to verify the correctness and effectiveness of the designed network automation